DECOLONIZATION OF THE MIND AS A PROCESS OF STATE RESOVEREIGNIZATION - Radanović, Srđan (Politeia, 2025)
Decolonization in the 1960s became a key aspect of political life, during which the concept itself was theoretically constituted. By the end of the Cold War, the concept expanded beyond the political domain into the realms of culture, education, and art, and in some cases, it became subject of relativization. One form of decolonization as liberation from the shackles of foreign rule is the decolonization of the mind. In this paper, alongside the presentation of key concepts, we will analyze the processes of colonization and decolonization of the mind through the lens of liberating the state ideological apparatus as a method of (re)sovereignization of the modern state. The removal of military and direct political presence of foreign powers from state territories did not mark the end of colonization, but rather its transformation through globalist processes, where the main roles are played by the economy, transnational corporations, and soft power—namely culture and all its forms. In neocolonialism, transnational corporations and the power of comprador elites are central to the colonization of the mind. We will present ways of resisting contemporary challenges that undermine national and cultural sovereignty through the process of decolonizing the mind—not limiting the scope solely to the Global South but extending it, in a universalist manner, to the states of contemporary Europe as well.
Keywords: Decolonization; resovereignization; neocolonialism; sovereignty